Atuação dos profissionais da saúde frente ao potencial doador de órgãos e tecidos em morte encefálica - Flores, Cíntia Maria Lovato (2021)
Introduction: The importance of early identification and maintenance of potential brain-dead organ and tissue donors provides a greater supply of organs and tissues for transplantation and improves the quality of life or allows greater survival for the recipient. Healthcare professionals must be involved at all stages of the organ donation process. This research aimed to understand how health professionals work in the process of identifying and maintaining the potential donor of organs and tissues in brain death and to contribute to the qualification of care practice in the organ donation process through educational actions, collaborating for the subsequent construction of an action plan. Method: The research used the methodological reference of Convergent Care Research. Data collection was between February 2020 and January 2021. The participants were twenty-six health professionals who work in the Adult Emergency Room of a general public teaching hospital in southern Brazil. Data collection was carried out through participant observation, semi-structured interviews, and convergence groups. We respected all ethical aspects involving research with human beings. Results: Four categories emerged from the data analysis: Feelings and motivations of health professionals facing the potential donor in brain death, in which professionals revealed that the process of organ and tissue donation is permeated by doubts and duality of feelings; Knowledge and practices of health professionals with a positive impact on the process of identifying potential brain death donors, related to agility in decisions and help and interaction between professionals in the institution; Challenges and interferences in the identification and maintenance of potential brain-dead donors such as the lack of knowledge and unpreparedness on the organ donation process; and Possibilities for the Development of the Identification and Maintenance Process of the potential brain death donor in the institution, in which the professionals suggested the development of an improvement plan. Conclusion: This study contributes to the opportunities for dialogue between health professionals about the reality of work in the theme and the suggestions for educational actions on the process of organ and tissue donation. It developed moments of reflection with health professionals, education on the topic, and development of strategies for the innovation of care practice such as the creation of flowcharts for the identification and diagnosis of BD, the maintenance of the potential donor and the organ donation process, besides an explanatory folder on brain death and organ donation in the institution. These materials will be a guide in the organ donation process and opportunities for change in care practice, already timidly viewed after the convergence group, which makes the Convergent Care Research method innovative in care practices in the medium and long term.